Pengaruh Brand Image dan Promosi Terhadap Keputusan Pembelian Produk Fashion Impor (Studi Kasus Pada Produk Uniqlo di Jakarta Utara) - Tamba, Rousdy Safari; Melita, Puput (Abiwara : Jurnal Vokasi Administrasi Bisnis, 2024)
This study was conducted with the aim to determine the effect of Brand image and promotion on the purchase decision of imported Fashion products (Case Study on Uniqlo products in North Jakarta). Respondents in this study are consumers who have used/purchased Uniqlo products at the North Jakarta branch store. The number of respondents used in this study amounted to 150 people. Data retreival, technique used is purposive sampling method with questionnaire tool distributed through google form. Testing data using multiple regression analysis techniques. The results of this study indicate that the independent variable is the Brand Image (X1) and promotion (X2) positive and significant effect on the dependent variable is the purchase decision (Y)